Kajian Mutu Limbah Ampas Tahu Segar dari Sentra Produksi Abian Tubuh - Fatimatuzzahrah, Baiq Shofi; Handayani, Baiq Rien; Nazaruddin, Nazaruddin; Bachmida, Elya Antariksana (Pro Food, 2024)
Tofu dreg, one of the by-products of tofu processing, still has high nutritional content to be used as a food source. Abian Tubuh Village as one of the tofu production centers in Mataram City has approximately 68 units of tofu producers with a considerable volume of tofu dreg. This research aimed to determine the chemical quality, microbial, and sensory by hedonic and scoring test of fresh tofu dreg from the Abian Tubuh production center was processed to make it suitable for use as a food ingredient. The research methods used were descriptive and experimental methods conducted in the laboratory using a one-factor completely randomized design. Data on chemical and organoleptic parameters were analyzed using ANOVA and further tested with Tukey’s HSD Test on the same significance level of 5%. Microbiological parameter data were analyzed with descriptive methods. The results showed that tofu producers in the Abian Tubuh production center produced tofu dregs with pH values, color, and texture significantly different from other samples. In contrast, Aw values, protein content, and aroma were not significantly different between samples. Ampas Tahu Bajang (ATB) produced tofu dregs with the best microbiological quality with total microbial growth of 3.1×105 CFU/g; total mold <1.0×102CFU/g; total coliform <3.0 APM/g and showed good organoleptic quality values both hedonic and scoring. All samples of tofu dregs from Abian Tubuh production centers do not contain harmful chemicals such as formalin and borax, so they are safe to use as food ingredients.